Konsepsi Kedaulatan Rakyat Dalam Cita Hukum Pancasila - Mexsasai Indra (Jurnal Selat, 2014)
Sovereignty of the people is placed in the context of political, legal ideals of Pancasila as stated in the preamble of the 1945 Constitution which boils down to, sovereignty, and prosperity of the people. accordance with the spirit of the precepts contained in the 4th Pancasila democracy that requires Indonesian-style democracy that is based on the notion “wisdom of deliberation representative” popular sovereignty in accordance with the ideals of Pancasila law can be seen from the construction of the founding fathers thought, that Indonesia’s democracy is a democracy that has its own characteristics, which is based on the principle of collectivism. Keywords: Sovereignty, law and the ideals of Pancasila